Asuhan Kebidanan Continuity Of Care (Coc) Pada Ny ”E” Umur 32 Tahun di Klinik Shazfa Mounira - Mafudiah, Lalita; Ari Andayani (Universitas Ngudi Waluyo, 2024)
Continuous midwifery care (continuity of care), namely providing midwifery care from pregnancy, delivery, postpartum, neonate until the decision to use family planning. This aims to help monitor and detect possible complications that accompany the mother and baby from pregnancy until the mother uses family planning. Midwifery care methods at the Shazfa Mounnira Clinic, and through home visits. The midwifery care provided to Mrs. In Mrs.